Group and Class Contexts for Learning and Support Online: Learning and affective support online in small group and class contexts - Anderson, Bill; Simpson, Mary (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
This study was designed to evaluate the use of asynchronous discussion in distance education in terms of student perceptions of its value for learning and for affective support. At the end of the third and sixth years of a distance delivered teacher education programme, students completed a survey to determine the extent to which the nature and characteristics of the online aspects of the programme contributed to learning and afforded affective support. Students perceived considerable value in the online interaction for both learning and support. Small groups and the whole class were seen as the dominant spaces for interaction, but there was considerable differentiation between them in terms of their contribution to affective support. The small group discussions were seen as most important for all aspects of communication but students reported non-participation by some members as a significant problem.